Cosmetic gynecology - positive impact mental and menstrual health: A case report. (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Cosmetic Gynecology practice has previously been labelled as purely esthetic and luxurybased. This case report demonstrates that this novel practice is useful for promoting positive mentalhealth and menstrual function.Case presentation: A 16-year-old nulliparous presented with esthetically displeasing results followinggenital surgery in childhood for a perineal mass with resultant posterior fourchette webbing. The estheticresult was noted to cause her mental distress and difficulty in tampon use. Correction of the untowardsurgical effect allowed easy tampon use, prevented future dyspareunia, and improved her overall mentalhealth.Discussion: Posterior fourchette webbing resulting from poor technique in labia minoraplasty leads tochronic perineal pain and dyspareunia. The resultant esthetics can also be displeasing. Surgical revisioncan alleviate these effects and improve self-esteem and mental health.Conclusion: Previously labeled as elective and occasionally unnecessary, cosmetic gynecology canimprove menstrual and reproductive function as well as mental health in women of reproductive age andadolescents.